The effect of low-density background plasma on frequency and energy characterictics of coaxial gyrotron cavity - Moskvitina, Yu.K.; Zaginaylov, G.I.; Tkachenko, V.I. (Вопросы атомной науки и техники, 2012)
The effect of low density background plasma on the electromagnetic field energy density in the ITER relevant coaxial gyrotron cavity is studied. The model of cold collisionless magnitoactive plasma is used. The dispersion relation and expression for the density of RF energy in plasma-filled coaxial gyrotron cavity are derived in the analytical form and analyzed numerically. It is shown that presence of low density plasma in coaxial gyrotron cavity leads to downshift of the operational frequency and to decreasing Ohmic loads of both the outer and inner conductors of coaxial gyrotron cavity.